I IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY PT. ANEKA TAMBANG Tbk BERDASARKAN POJK NO.51/POJK.03/2017 - Marten Puyo; Ika Makherta Sutadji; Nina Indriastuty (KRISNA: Kumpulan Riset Akuntansi, 2024)
The aim of this research is to provide information and understanding regarding the implementation of corporate social responsibility (CSR) reporting in the sustainability report. This research was conducted to understand the things that the company has done and disclosed in the Sustainability Report in carrying out the CSR Program. The subject of this research is PT. Aneka Tambang Tbk, using the 2022 Sustainability Report. This report refers to the provisions of the Indonesian government as outlined in POJK No. 51/POJK.03/2017. The research method used in the research is descriptive-qualitative. The conclusion from the results of this research is that PT. Aneka Tambang Tbk has tried to meet the standards of the Indonesian government. The practices that have been carried out so far have reflected CSR activities and other things that have not been stated in the Sustainability Report. PT. Aneka Tambang Tbk has implemented practices that are beneficial for the environment and society in the long term to contribute to Indonesia's Sustainable Development Goals